Design and Development of a Mobile Soil Profile Digitizer - Wee, Beng Sui (2004)
This study describes the design and development of an automated, mobile-type 2-axis laser soil surface profile digitizer for 3D mapping of soil surface. The construction of the digitizer consists of 2 main parts, the measurement apparatus and a special design trailer. The measurement apparatus provides the non-contact soil surface digitizing and the special design hydraulically powered open-base trailer is used for transporting, uplifting or releasing the measurement apparatus during field operation. The digitizer was pulled by a Massey Ferguson 3060 Instrumented agricultural tractor. Three PLC controlled stepper motors and 3 sets of precision ball screw carriage mechanism were used to drive the sensor in 2-axis of digitizing direction. Dewe-2010 PC Instrument was employed to perform the data acquisition and user control task for the digitizer. The simplified method of the user control interface integrates the concept of touch-screen virtual control panel built on Dasylab V5b.5@ programming platform. The Digitizer was capable to digitize a maximum area of 1.05m x 1.8m with an adjustable digitizing speed, digitizing interval and digitizing area to suit with the required operation time and output resolution. Field tests were conducted to determine adequate digitizing speed and digitizing interval for the digitizer, and also to evaluate the significant of tillage operations, tractor travel speeds and rotary tiller's speeds with respect to average elevation height, Degree of Tilth, and Random Roughness Index of the soil surface profile, and sensing error of the digitizer. Result from field test showed that implement types, tractor travel speed, and rotary tiller speed had significant effects on random roughness index of the soil surface profile. Implement types had only significant effect on the sensing error of the digitizer and rotary tiller speed had only significant effect the Degree of Tilth of the soil surface profile.